Clinical outcomes of deferred revascularisation using fractional flow reserve in patients with and without diabetes mellitus. Issue 1 (December 2016) - Kennedy, Mark; Kaplan, Eliza; Hermanides, Rik; Fabris, Enrico; Hemradj, Veemal; Koopmans, Petra; Dambrink, Jan-Hank; Marcel Gosselink, A.; van't Hof, Arnoud; Ottervanger, Jan; Roolvink, Vincent; Remkes, Wouter; et al.
Abstract Objective Deferred revascularisation based upon fractional flow reserve (FFR >0.80) is associated with a low incidence of target lesion failure (TLF). Whether deferred revascularisation is also as safe in diabetes mellitus (DM) patients is unknown. Methods All DM patients and the next consecutive Non-DM patients who underwent a FFR-assessment between 1/01/2010 and 31/12/2013 were included, and followed until 1/07/2015. Patients with lesions FFR >0.80 were analysed according to the presence vs. absence of DM, while patients who underwent index revascularisation in FFR-assessed or other lesions were excluded. The primary endpoint was the incidence of TLF; a composite of target lesion revascularisation (TLR) and target vessel myocardial infarction (TVMI). Results A total of 250 patients (122 DM, 128 non-DM) who underwent deferred revascularisation of all lesions (FFR >0.80) were compared. At a mean follow up of 39.8 ± 16.3 months, DM patients compared to non-DM had a higher TLF rate, 18.1 vs 7.5 %, logrank p ≤ 0.01, Cox regression-adjusted HR 3.65 (95 % CI 1.40–9.53, p < 0.01), which was largely driven by a higher incidence of TLR (17.2 vs. 7.5 %, HR 3.52, 95 % CI 1.34–9.30, p = 0.01), whilst a non-significant but numerically higher incidence of TVMI (6.1 vs. 2.0 %, HR 3.34, 95 % CI 0.64–17.30, p = 0.15) was observed. Conclusions This study, the largest to directly compare the clinical outcomes of FFR-guided deferred revascularisation in patients with and without DM, shows that DM patients are associated with a significantly higher TLF rate. Whether intravascular imaging, additional invasive haemodynamics or stringent risk factor modification may impact on this higher TLF rate remains unknown.